Enhancing Social Studies Achievement through the Make a Match Cooperative Model: The Moderating Role of Student Motivation - Herma Kurnia Putri; Eko Risdianto; Adityas Agung Ramandani (WISE Pendidikan Indonesia, 2025)
This study investigates the effectiveness of the Make a Match cooperative learning model in enhancing social studies achievement among seventh-grade students, while considering student motivation as a moderating variable. Employing a quasi-experimental design with a pretest-posttest control group, the study involved 84 students from Al-Azhar 3 Junior High School in Bandar Lampung, Indonesia, who were divided into experimental and control groups using cluster random sampling. Data were collected through a validated achievement test and a motivation questionnaire, then analyzed using ANOVA and independent samples t-tests. The findings indicate that the Make a Match model significantly improves student learning outcomes compared to traditional methods, particularly for students with high motivation. Conversely, students with low motivation benefited more from the Jigsaw model, highlighting a critical interaction effect between instructional strategy and learner characteristics. These results underscore the importance of aligning pedagogical approaches with students’ motivational profiles to optimize academic achievement. The study contributes to the literature on differentiated instruction and cooperative learning by emphasizing the nuanced interplay between teaching methods and student motivation.